2018
DOI: 10.2139/ssrn.3155827
|View full text |Cite
|
Sign up to set email alerts
|

Budding Yeast Has a Minimal Endomembrane System

Abstract: The endomembrane system consists of the secretory and endocytic pathways, which communicate by transport to and from the trans-Golgi network (TGN). In mammalian cells, the endocytic pathway includes early, late, and recycling endosomes. In budding yeast, different types of endosomes have been described, but the organization of the endocytic pathway has been unclear. We performed a spatial and temporal analysis of yeast endosomal markers and endocytic cargoes. Our results indicate that the yeast TGN also serves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 93 publications
(53 reference statements)
7
38
1
4
Order By: Relevance
“…To determine if increased recycling of endocytosed proteins is responsible for the elevated cargo concentration observed at cell surfaces in the absence of Vps4, we generated vps4 Δ rcy1 Δ double mutant strains expressing Ste3‐, Mep3‐ or Ptr2‐GFP. Rcy1 is involved in the recycling of endocytosed proteins, aiding in the return of cargo from endosomes to the PM 60 ; because recent reports suggest that yeast is devoid of early endosomes and that the functions of these organelles are instead carried out at the trans ‐Golgi network, this path may in fact be from Golgi to PM 10 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if increased recycling of endocytosed proteins is responsible for the elevated cargo concentration observed at cell surfaces in the absence of Vps4, we generated vps4 Δ rcy1 Δ double mutant strains expressing Ste3‐, Mep3‐ or Ptr2‐GFP. Rcy1 is involved in the recycling of endocytosed proteins, aiding in the return of cargo from endosomes to the PM 60 ; because recent reports suggest that yeast is devoid of early endosomes and that the functions of these organelles are instead carried out at the trans ‐Golgi network, this path may in fact be from Golgi to PM 10 …”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these structures are enlarged early or recycling endosomes, or exaggerated versions of the prevacuolar organelles normally observed in class E mutants. However, if new thinking regarding the yeast endomembrane system is correct in that the trans ‐Golgi supports early and recycling endosome functions, 10 it is possible that they are, instead, expanded trans ‐Golgi networks, especially since prior studies have shown that Rcy1 acts with Drs2 at the Golgi to promote endocytic recycling 61‐63 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En estos microorganismos la distinción entre TGN y endosomas tempranos ha resultado siempre complicada. En este sentido, un estudio reciente ha establecido que los endosomas tempranos se corresponden en realidad con diferentes estadios de maduración del TGN (Day et al, 2018 (Cowles et al, 1997;Frankel and Audhya, 2018;Stepp et al, 1997).…”
Section: Diferencias Entre Los Modelos De Sistema Endosomal De Mamífeunclassified
“…Abreviaturas: RE, retículo endoplásmico; TGN, red trans del Golgi; PM, membrana plasmática; y PVE, endosoma prevacuolar. Adaptado de Day et al, 2018. B: Parte superior: Representación de la estructura de un trisquelión.…”
Section: Tráfico Mediado Por Clatrina Los Adaptadoresunclassified